2016
DOI: 10.1038/srep33500
|View full text |Cite
|
Sign up to set email alerts
|

SCOP/PHLPP1β in the basolateral amygdala regulates circadian expression of mouse anxiety-like behavior

Abstract: While disruption of the circadian clock triggers a spectrum of affective abnormalities, how the clock regulates mammalian emotionality remains unclear. Here, we characterized the time-of-day-dependent regulation of mouse anxiety-like behaviors. We show that anxiety-like behaviors are expressed in a circadian manner in mice and demonstrate that the clock machineries in the dorsal telencephalon (dTel) are required for the time-of-day-dependent regulation of anxiety-like behaviors. We identify suprachiasmatic nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 47 publications
2
13
0
Order By: Relevance
“…Assessing behaviors in the dark cycle is more physiologically relevant for feeding and minimizes stresses associated with the external environment and fasting, which impose sex-specific effects in mice and humans (described above). However, reported effects of diurnal factors on anxiety-like behavior are inconsistent, and are sex and assay dependent ( Richetto et al, 2019 ; Nakano et al, 2016 ). Here, we found that performing the NSF assay at the start of the dark cycle promoted hyperphagic responses in both sexes.…”
Section: Discussionmentioning
confidence: 99%
“…Assessing behaviors in the dark cycle is more physiologically relevant for feeding and minimizes stresses associated with the external environment and fasting, which impose sex-specific effects in mice and humans (described above). However, reported effects of diurnal factors on anxiety-like behavior are inconsistent, and are sex and assay dependent ( Richetto et al, 2019 ; Nakano et al, 2016 ). Here, we found that performing the NSF assay at the start of the dark cycle promoted hyperphagic responses in both sexes.…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies explore anxiety across time of day 16 . Previous studies provide evidence that the expression of suprachiasmatic nucleus circadian oscillatory protein (SCOP) in the basolateral amygdala plays a key role in generating circadian rhythmicity in anxiety-like behavior 17 . Other studies show melatonin is involved in the anxiety response of diurnal and nocturnal species 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Pioneered by McClung et al the contribution of local clocks in the ventral tegmental area and nucleus accumbens, which constitute the mesolimbic dopaminergic pathway, in mood regulation has been well-characterized (McClung et al, 2005 ; Roybal et al, 2007 ; Mukherjee et al, 2010 ; Spencer et al, 2013 ; Chung et al, 2014 ). More recently, Shimizu et al reported that the suprachiasmatic nucleus circadian oscillatory protein (SCOP) mediates the circadian regulation of long-term memory formation by local clocks in the hippocampus (Shimizu et al, 2016 ), and Nakano et al, found that the same molecule regulates the circadian expression of anxiety-like behavior under the control of local clocks in the basolateral amygdala (Nakano et al, 2016 ). On another front, Yu et al reported that Bmal1 -dependent local clock in histaminergic neurons of tuberomammillary nucleus (TMN) regulate sleep architecture, likely via transcriptional control of the histidine decarboxylase gene, which encodes a histamine-synthesizing enzyme, but is not involved in regulating circadian rhythms (Yu et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cell type-specific manipulations of clock genes have clarified the roles of peripheral circadian clocks in a variety of tissues (McDearmon et al, 2006 ; Storch et al, 2007 ; Lamia et al, 2008 ; Westgate et al, 2008 ; Dibner et al, 2010 ; Marcheva et al, 2010 ; Sadacca et al, 2011 ; Fustin et al, 2012 ; Paschos et al, 2012 ; Nguyen et al, 2013 ; Gibbs et al, 2014 ; Jacobi et al, 2015 ; Xie et al, 2015 ; Dudek et al, 2016 ; Xu et al, 2016 ). By contrast, knowledge of the physiological roles of brain clocks in extra-SCN regions remains limited (Roybal et al, 2007 ; Mukherjee et al, 2010 ; Mieda and Sakurai, 2011 ; Spencer et al, 2013 ; Yu et al, 2014 ; Nakano et al, 2016 ; Orozco-Solis et al, 2016 ; Shimizu et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%